2016
DOI: 10.1021/acs.jafc.6b02250
|View full text |Cite
|
Sign up to set email alerts
|

Potent Nematicidal Activity of Maleimide Derivatives on Meloidogyne incognita

Abstract: Different maleimide derivatives were synthesized and assayed for their in vitro activity on the soil inhabiting, plant-parasitic nematode Meloidogyne incognita, also known as root-knot nematode. The compounds maleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-isobutylmaleimide showed the strongest nematicidal activity on the second stage juveniles of the root-knot nematode with EC50/72h values of 2.6 ± 1.3, 5.1 ± 3.4, 16.2 ± 5.4, and 19.0 ± 9.0 mg/L, respectively. We also determined the nematicidal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Treatment of helminths with aryl hydrazones and maleimide derivatives altered their metabolic profile by changing fatty acids and rates of ammonia elimination (Eloh et al, 2015, 2016) giving insight into the mode of action of phenolic derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of helminths with aryl hydrazones and maleimide derivatives altered their metabolic profile by changing fatty acids and rates of ammonia elimination (Eloh et al, 2015, 2016) giving insight into the mode of action of phenolic derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the nematicidal activity of copper sulfate has been determined at EC 50/24h = 32.9 μg/mL, the potent activity of CuFe NPs could partially be attributed to copper ions released 24 hours after dispersion of CuFe NPs in water. On the contrary iron has not significant antimicrobial properties [43], while the nematicidal activity of iron sulfate against M. incognita has been reported at 126 ± 48 μg/mL [39], much higher than the concentration of free iron (0.5 μg/mL) released after 24 h of dispersion and therefore the effect of copper/iron based while the bimetallic CuFe NPs resulted in significant increase of fresh shoot and root weight in the three higher doses, indicate an additional beneficial role (Figure 5) (Table 5) and should be considered together with the efficacy parameters in case it would be addressed as a pest management tool.…”
Section: Discussionmentioning
confidence: 98%
“…The nematicidal activity of the NPs was determined in the descending order of CuFe (Cu 0 ) > Cu (Cu 0 ) = CuFeO 2 (Cu 1+ ), with the last two compositions revealing similar efficacy. Copper salts have already been reported of nematicidal activity when used in combination with maleimide derivatives [39], while metal complexes have been found effective both against the root-knot nematodes and the soil born fungi Fusarium oxysporum [40]. In specific copper sulphate, principally used as a fungicide but also for treating copper-deficient soils, has been reported to exhibit an EC 50 value of 280 μg/mL against M. javanica [41] while Eloh et al [39] reported an EC 50 value of 48.6 μg/mL against M. incognita.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual economic losses owing to nematode infection of crop production are estimated at $173 billion [ 1 ]. These are parasitic to a variety of crops such as cucumber, melon, pepper, tomato and fruit, and infect the entire plant including the roots, stems, leaves, flowers, fruit and seeds [ 2 , 3 ]. This scenario demands further research to identify effective albeit environment-friendly alternatives to replace legislatively withdrawn highly toxic nematicides [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%